Pelatihan Kelompok Sadar Wisata Kabupaten Landak - Tuminah Tuminah; Mustika Aji Hertanto; Yustina Selong; Antonius Setyawan Sugeng Nur Agung; Albert Rufinus; Yudas Alno (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Landak Regency in the province of West Kalimantan is rich in beautiful natural tourist attractions. Limited human resources and lack of infrastructure affect the development needed to manage those places properly. However, Landak has 12 communities that support local tourism, known as Kelompok Sadar Wisata (Pokdarwis), in each subdistrict. They are to be good beginning pioneers to manage the local tourist attractions. Helping them, STKIP Pamane Talino in collaboration with Dinas Pemuda Olahraga dan Pariwisata Landak (Disporapar) provide them training on how to be a good tour guide as our community service. They are expected to have more skills and knowledge to recognize and develop any gift and potential in their village. They will be the leader of their Pokdarwis. The implementation of this community service has been done through several stages: taking surveys, interviewing residents and community leaders, training on Sapta Pesona and tour guide, and preparing the final report. This activity results in the growth of public awareness, especially among members of the Pokdarwis, in developing and maintaining local tourist attractions.